Workshop Pembuatan dan Aplikasi Penggunaan Relay Pengganti Staircase pada Instalasi Penerangan di SMKN 1 Sumbar - Tri, Tri Artono; Riza Widia; Dedi Erawadi; Aldi Rahman; Yuhaidizen; Abdul Manan; Faris Giats (Electrical Engineering Department Faculty of Engineering Universitas Andalas, 2024)
In the practicum, SMKN 1 West Sumatra has used various types of switches but has not used a Staircase Switch or a Relay to Relay pengganti Saklar Staircase. As we know, switches are electrical devices with various types, purposes and different usage situations. In general, switches are divided into two, namely manual and automatic switches. Manual switches require physical action from the user but automatic switches work automatically based on certain automatic settings. Through this Community Service, the team from the Padang State Polytechnic D3 Electrical Engineering Study Program is trying to introduce Staircase Switches and Relay pengganti Saklar Staircase. It is hoped that it can contribute to science and technology that can be used in practicums by SMKN 1 West Sumatra, especially the Electrical Power Installation Engineering Expertise Program. In implementing this community service using a workshop method where the participants are teachers and students, the team explained in detail about the Relay pengganti Saklar Staircase and training on how to use it. Based on the results of the workshop and questionnaire, this switch is very suitable for use in the practical work of the Electrical Power Installation Engineering Skills Program at SMKN 1 West Sumatra because this switch is designed with user friendly principles, has a timer feature with high accuracy, a time display indicator and a simple wiring circuit. Through this community service, the Team from the D.3 Electrical Engineering Study Program grant a Relay pengganti Saklar Staircase unit to SMKN 1 West Sumatra as a form of technology transfer and development of learning materials.